2006
DOI: 10.2165/00822942-200605020-00003
|View full text |Cite
|
Sign up to set email alerts
|

RefSeq Refinements of UniGene-Based Gene Matching Improve the Correlation of Expression Measurements Between Two Microarray Platforms

Abstract: Matching genes across microarray platforms is a critical step in meta-analysis. Standard practice uses UniGene to match genes. Numerous studies have found poor correlations between platforms when using UniGene matching. We profiled samples from 33 breast cancer patients on two different microarray platforms (Affymetrix and cDNA) and investigated gene matching. Our results confirmed that UniGene-based matching led to poor correlations of gene expression between platforms. Using RefSeq, a database maintained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Because genomic and transcript sequences are continuously updated, mappings become inaccurate with time. In this study we have found, as previously noted, that different annotation tools [29,30], as well as different annotation methods yield different results [34]. It has been reported that matching genes at the sequence level is more efficient than identifier-based mappings [35,36].…”
Section: Discussionsupporting
confidence: 61%
“…Because genomic and transcript sequences are continuously updated, mappings become inaccurate with time. In this study we have found, as previously noted, that different annotation tools [29,30], as well as different annotation methods yield different results [34]. It has been reported that matching genes at the sequence level is more efficient than identifier-based mappings [35,36].…”
Section: Discussionsupporting
confidence: 61%
“…The situation can be improved when matching of genes is sought using genomic sequence rather than sequences inferred from the Unigene database of transcripts (http://www.ncbi.nlm.nih.gov/unigene) 54 . Concordance between platforms is improved further when probes are compared only when they target overlapping transcript sequence regions on cDNA microarrays or gene-chips 55 .…”
Section: Potential Limitations and Future Directionsmentioning
confidence: 99%
“…This difference between UniGene and RefSeq results, albeit small, is likely due to the different methods of identifying and assigning transcripts used in the process, and has been observed in prior studies also [4], [5], [6], [7], [8], [9], [10]. Even though we did observe variability due to different laboratory protocols as seen by previous studies, a superior correlation between tissues with similar sources of cells was able to surpass this limitation and make the meta-analysis scientifically useful.…”
Section: Discussionmentioning
confidence: 80%
“…UniGene IDs have been used as the matching criterion to merge data across various platforms, but this has led to a substantial portion of the data remaining unmatched in previous studies [4], [5], [6], [7], [8]. Recent approaches have tried using Reference Sequence (RefSeq) IDs as the matching criterion [9]. RefSeq is a public access database, also maintained by NCBI.…”
Section: Introductionmentioning
confidence: 99%